Functional Nanocomposites: From Strategic Design to Applications - Li Cao; Mohammed J. Meziani (Nanomaterials)
Nanomaterials with one-, two-, or three-dimensional structures have exhibited superior optical, electronic, magnetic, thermal, and mechanical properties compared to their bulk material counterparts [...]